2012
DOI: 10.1371/journal.pgen.1002612
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of a Mapping Population Exposes New Insights in the Regulation of Seed Metabolism and Seed, Fruit, and Plant Relations

Abstract: To investigate the regulation of seed metabolism and to estimate the degree of metabolic natural variability, metabolite profiling and network analysis were applied to a collection of 76 different homozygous tomato introgression lines (ILs) grown in the field in two consecutive harvest seasons. Factorial ANOVA confirmed the presence of 30 metabolite quantitative trait loci (mQTL). Amino acid contents displayed a high degree of variability across the population, with similar patterns across the two seasons, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
127
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(150 citation statements)
references
References 95 publications
(115 reference statements)
20
127
3
Order By: Relevance
“…The heritability values obtained in our analysis resemble those in previous studies of metabolic traits in Arabidopsis, tomato (Solanum lycopersicum), and wheat (Triticum aestivum) (Kliebenstein et al, 2001a;Keurentjes et al, 2006;Toubiana et al, 2012;Alseekh et al, 2015;Matros et al, 2017). Broad-sense heritability (H 2 ) for biomass, structural components, metabolites, and several enzyme activities (aINV, nINV, PEPC, AGP, UGP, NRVs, and GDH) was moderate to high (20-74%), with marker-based h 2 (Kruijer et al, 2015) very close to H 2 values.…”
Section: Discussionsupporting
confidence: 83%
“…The heritability values obtained in our analysis resemble those in previous studies of metabolic traits in Arabidopsis, tomato (Solanum lycopersicum), and wheat (Triticum aestivum) (Kliebenstein et al, 2001a;Keurentjes et al, 2006;Toubiana et al, 2012;Alseekh et al, 2015;Matros et al, 2017). Broad-sense heritability (H 2 ) for biomass, structural components, metabolites, and several enzyme activities (aINV, nINV, PEPC, AGP, UGP, NRVs, and GDH) was moderate to high (20-74%), with marker-based h 2 (Kruijer et al, 2015) very close to H 2 values.…”
Section: Discussionsupporting
confidence: 83%
“…populations with many previous examples being published in Arabidopsis, potato, and maize (Rowe et al, 2008;Lisec et al, 2011;Carreno-Quintero et al, 2013), as well as for a range of different traits and tissue types in this very tomato population (Schauer et al, , 2008Toubiana et al, 2012). However, this study revealed several novel insights concerning the interrelation of traits from primary and secondary metabolism with yieldassociated traits.…”
Section: Discussionmentioning
confidence: 61%
“…Tissue-specific accumulation of metabolites, representing one of the main contributions to metabolite diversity, is of great interest to plant scientists (Schilmiller et al, 2010;Chan et al, 2011;Watanabe et al, 2013). Metabolic diversity between different tissues might arise from differences in spatial-temporal expression of genes (Kim et al, 2012;Thatcher et al, 2014) and in some cases by duplicate genes that display spatially or temporally distinct expression patterns (Toubiana et al, 2012;Matsuba et al, 2013). By comparing genetically controlled natural variation of PAs in different tissues at high resolution, we have shown that although coordinated genetic control across various tissues can be observed for some PAs, the majority of the loci were obtained in a tissue-specific manner (Supplemental Table 4), suggesting distinct regulation underlying the metabolic readout between tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the enormous diversity of specialized metabolites in plants comes from modifications or decorations of core structures by different tailing reactions such as acylation (Bontpart et al, 2015), glycosylation (Bowles et al, 2005), methylation (Lam et al, 2007), and so on (Schwab, 2003). In addition, many studies have revealed that plant specialized metabolites accumulate with tissue specificity (Schilmiller et al, 2010;McDowell et al, 2011;Kim et al, 2012;Toubiana et al, 2012;Watanabe et al, 2013;Dong et al, 2015;Wen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%